Into the Grey - Kiernan, Celine (Candlewick Press, 2014)
Set in Ireland in the early 1970s, this story stars twin brothers Patrick and Dom Finnerty, who have their world turned upside down when their house and all they possess is burned to the ground. Displaced, the family moves into their summer seaside cottage. Now in the middle of winter, the cottage seems dull, bleak, and quite eerie. Suffering from horrible nightmares, the boys' bond of brotherly love is put to the test when they discover that the "goblin-boy" is not just a dream. When Patrick tries to rid them of the ghostly creature, it takes possession of Dom instead. Patrick realizes that in order to save his brother's life he must befriend this ghost and figure out what it wants and why before time runs out. The protagonist's journey of self-discovery uncovers numerous family secrets, forges unlikely allies, and proves that the power of friendship, loyalty, and love are far stronger than he ever imagined. Kiernan's beautiful and haunting novel is full of mystery and suspense with continuous plot twists and turns. The narrative voice is compelling and honest while capturing the emotional terror the teen has to face. The refreshing, multidimensional characters drive the story line and readers will connect with them because of the poignant and touching moments. A captivating read that combines Irish history with the supernatural. -- Donna Rosenblum, Floral Park Memorial High School, NY -- From School Library Journal, Amazon.com